Volunteered geographic information: interpretation, visualization and social context - Burghardt, Dirk; Demidova, Elena; Keim, Daniel (Springer Nature Switzerland, 2024)
Part I: Representation and Analysis of VGI -- 1. WorldKG: World-Scale Completion of Geographic Information -- 2. Analyzing and Improving the Quality and Fitness for Purpose of OpenStreetMap as Labels in Remote Sensing Applications -- 3. Efficient Mining of Volunteered Trajectory Data Sets -- 4. Uncertainty-Aware Enrichment of Animal Movement Trajectories by VGI -- 5. Two Worlds in One Network: Fusing Deep Learning and Random Forests for Classification and Object Detection -- Part II: Geovisualization and User Interactions Related to VGI -- 6. Toward Visually Analyzing Dynamic Social Messages and News Articles Containing Geo-Referenced Information -- 7. Visually Reporting Geographic Data Insights as Integrated Visual and Textual Representations -- 8. Effects of Landmark Position and Design in VGI Based Maps on Visual Attention and Cognitive Processing -- 9. Addressing Landmark Uncertainty in VGI-based Maps: Approaches to Improve Orientation and Navigation Performance -- 10. Improvement of Task-Oriented Visual Interpretation of VGI Point Data -- Part III: Active Participation, Social Context and Privacy Awareness -- 11. Environmental Tracking for Healthy Mobility -- 12. Extraction and Visually Driven Analysis of VGI for Understanding People’s Behavior in Relation to Multi-Faceted Context -- 13. Digital Volunteers in Disaster Management -- 14. Protecting Privacy in Volunteered Geographic Information Processing.